교양교육의 명칭 재정립을 통한 교양교육의 재개념화 - 백승수(Paek, Seung Su) (교양교육연구, 2019)
교양교육의 명칭 문제는 해묵은 숙제다. 다양한 용어들이 오 ‧ 남용되면서 교양교육에 대한 수 많은 오해와 정체성 혼란을 초래하고 있다. 번역어로서의 교양교육은 일본, 독일, 미국의 영향을 차례로 받으면서 애매모호한 명칭으로 번역되었다. 개념적으로도 자유교육, 인문교육, 기초교육, 일반교육을 동시에 추구하는 복합적 개념이 되었다. 교양교육이라는 현재의 명칭은 애매성, 모호 성, 혼란성, 복잡성, 제한성의 문제점을 노출하고 있다. 교양교육에 대한 왜곡된 인식을 바로잡고, 정체성, 보편성, 간결성, 용의성의 원칙에 충실한 새 로운 명칭을 모색해야 할 시기이다. 교육의 목적을 명료하게 나타내고, 교육의 내용을 분명하게 제시하며, 교육의 주체를 확실하게 드러낼 수 있는 새로운 명칭이 절실하다. 명칭 재정립의 방향 과 원칙을 확인하고, 새로운 교양교육의 명칭으로 ‘문리교육’을 제안한다. 문리교육은 ‘인문학 ‧ 사 회과학 ‧ 자연과학의 기초학문분야를 가로지르는 학제 횡단적 교양교육’이다. 문리교육은 새로운 교양교육, 정상화된 교양교육, 강화된 교양교육을 지향한다. 교양교육의 명칭을 바르게 하는 것만으로도 교양교육의 여러 문제를 해결할 수 있을 것이다. 교양교육 공동체의 시의적절한 공론화가 필요하다. The appellation of general education has been a perennial issue. Abuse and misuse of varied terms have caused a host of misunderstandings and identity crises on general education. As the term general education as a translated word has been influenced by in order of Japan, Germany, and the US, it has been translated into ambiguous appellations. It has also become conceptually complex that seeks liberal education, humane education, basic education, and general education simultaneously. The current appellation of general education has problems exposed with ambiguity, vagueness, confusion, complexity, and limitations. It is necessary to correct biased awareness on general education and to find a new appellation committed to principles of identity, universality, brevity, and ease of use. It is urgently needed to coin a new appellation that clearly shows purpose of education, suggests contents of education and definitely indicates subject of education. Identifying the directivity and principles of reestablishing the appellation, this study suggests ‘liberal arts education’ as a new appellation of general education. Liberal arts education is ‘general education subject to cross-sectional school system throughout basic studies of humanities, social science, and natural science.’ Liberal arts education pursues new, normalized and intensified general education. Correcting the appellation of general education alone would solve a lot of problems in general education. It should be forehandedly publicized by community of general education. KCI Citation Count: 9